Metachronous Malingnancy, 27 Years After Teflon Cordal Injection - Bottazzoli, Marco; Marcantoni, Alessandra; Picori, Lorena; Grandi, Cesare; Chierichetti, Franca; Donner, Davide (Archives of Clinical and Medical Case Reports, 2019)
We report a rare case of a patient known for a long-time history of iatrogenic VC paralysis, with unusual PET-CT findings. Due to a bilateral paragangliomas (PGLs), 27 years before the patient underwent a left jugulo-petrosectomy. After admission for contralateral sudden hearing loss, MRI and PET-CT scans were acquired. We tried to critically analyze the clinical relevance of multimodal imaging in an unusual condition of comorbities. Moreover, we suggested a physiopathological interpretation of collecting imagings and clinical otorhinolaryngological aspects. We could determine that high SUV in paralyzed left VC was related to a foreign-body reaction after laryngeal injection by polytetrafluoroethylene fluoropolymer resin (Teflon) performed 27 years before. Moreover, an asymptomatic pT1c mixed lung adenocarcinoma was serendipitously detected in the left lung. The SUVs of these two lesions were both compatible with neoplasms. A further possible lesion in the right lung highlighted by MRI was not confirmed by PET-CT imaging (MRI artifact). Although Teflon is no longer in use for laryngeal injection, clinicians should be aware of the potential misinterpretation laryngeal findings in patients with such a clinical history, even long time after the procedure.